2016
DOI: 10.1111/nyas.13059
|View full text |Cite
|
Sign up to set email alerts
|

Targeted heat shock protein 72 for pulmonary cytoprotection

Abstract: Heat shock protein 72 (HSP72) is perhaps the most important member of the HSP70 family of proteins, given that it is induced in a wide variety of tissues and cells to combat stress, particularly oxidative stress. Here we review independent observations of the critical role this protein plays as a pulmonary cytoprotectant and discuss the merits of developing HSP72 as a therapeutic for rapid delivery to cells and tissues after a traumatic event. We also discuss the fusion of HSP72 to a cell-penetrating single-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…During tendon damage and collagen synthesis, the cells that have multiple fibripositors and cytoplasmic protrusions can be found in the area [4]. HSP72 is the most important member of the heat-shock protein family [24]. Studies have confirmed that when body cells are subjected to stressful conditions, such as hyperpyrexia, oxidation, and mechanical damage, the increased expression of HSP72 can strengthen the tolerance of cells to damage, improve the viability of the cells, and reduce cell necrosis or apoptosis caused by stress injury [25].…”
Section: Discussionmentioning
confidence: 99%
“…During tendon damage and collagen synthesis, the cells that have multiple fibripositors and cytoplasmic protrusions can be found in the area [4]. HSP72 is the most important member of the heat-shock protein family [24]. Studies have confirmed that when body cells are subjected to stressful conditions, such as hyperpyrexia, oxidation, and mechanical damage, the increased expression of HSP72 can strengthen the tolerance of cells to damage, improve the viability of the cells, and reduce cell necrosis or apoptosis caused by stress injury [25].…”
Section: Discussionmentioning
confidence: 99%
“…We also screened an important cellular target of the nicotine metabolite cotinine, gelsolin, which may affect basic tumour transformation and metastasis processes, such as migration and apoptosis, through gelatine ( Nowak et al, 2015 ). Heat shock protein, on the other hand, is reported to be a major marker affected by cigarette smoke and is involved in signalling pathways associated with the cell cycle, cell death and inflammation ( Gál et al., 2011 ; Hulina-Tomašković et al., 2019 ; Parseghian, Hobson & Richieri, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also screened an important cellular target of the nicotine metabolite cotinine, gelsolin, which may affect basic processes of tumor transformation and metastasis, such as migration and apoptosis, through gelatin [41] . Heat shock protein, on the other hand, is reported to be a major marker affected by cigarette smoke and is involved in signaling pathways for the cell cycle and cell death and inflammation [42]- [44] .…”
Section: Discussionmentioning
confidence: 99%